Motor Control Mechanisms and the Practice of Krav Maga-a Narrative Analysis - Guy Mor (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2021)
Krav Maga ('contact combat') is an Israeli hand-to-hand combat discipline that originated in the early 19th century in response to life-threatening conflicts. Today, Krav Maga is a popular self-defense and martial art discipline practiced and taught throughout the world. One of the key features of Krav Maga that distinguishes it from other combat disciplines is its dependence on reflexive defense - a natural and immediate defensive reaction. However, the relevant literature has not discussed the motor control mechanisms that underlie reflexive defense in hand-to-hand combat or that account for its temporal characteristics. This introductory study argues that the reflexive defense at the core of Krav Maga is a genuine reflex mediated at the brainstem level. The paper also discusses some aspects of reaction in the context of self-defense and combat sports, and the implications for the debate on whether Krav Maga training should involve more than one combat response to any given threat.